(untitled) (Eurasian Medical Research Periodical, 2023)
Type 2 diabetes mellitus (DM) is one of the most common noncommunicable diseases on the globe. If at present the number of patients with diabetes in the world is 347 million people, then by 2025, according to scientists, this figure will reach at least 592 million, of which 90% will be in diabetes. Global trends in the incidence of type 2 diabetes are also observed in Uzbekistan.